The effects of passenger loading and ventilation air on airflow patterns within an aircraft cabin - Madden, Michael Levi (Kansas State University, 2015)
With the increasing number of passengers traveling on commercial aircraft, it is important to mitigate the possibility of diseases and contaminants spreading throughout aircraft cabins and becoming harmful to the health of passengers. The ventilation system on a Boeing 767 aircraft is designed to create lateral flow to isolate contaminants to a single row of the cabin and remove the harmful air quickly. There are many variables that can influence the airflow patterns inside the cabin. The thermal plumes created by occupants are one of the variables investigated in this experimentation. Another special case investigated is the transport of gases in the cabin when the ventilation air is eliminated. Experimentation is performed in a mock-up Boeing 767 cabin. The mock-up enclosure consists of 11 rows and 7 columns of seats in each row. Ventilation apparatus, seating, and cabin dimensions used for testing are all representative of an actual aircraft. Thermal manikins are placed in the cabin seats to simulate the heat load from a seated person. A mixture of carbon dioxide (CO²) and helium (He) is injected into the cabin as a tracer gas to simulate the release of contaminants. The CO² concentration is measured by analyzers placed at the cabin inlet, exhaust, and seat of interest. The tracer gas can be injected and sampled at any of the 77 seats. In order to determine the effects of passenger density, testing is performed with maximum occupant load and repeated with half of the passenger load. Tracer gas is injected in three locations of the cabin and sampled in 32 seats for each injection seat. The testing revealed a significant effect of passenger load on airflow patterns. To determine the effects of removing the ventilation air, the cabin is supplied with 1400 cfm of outdoor air at 60°F for three hours to bring the cabin to a steady state temperature. Then, the supply air is shut off, and tracer gas is injected into the cabin and the CO² concentration is sampled at 12 locations throughout the cabin. It was found that contaminants are still transported throughout the cabin without the ventilation air.
Keywords: Contaminant; Transport; Passenger; VentilationAircraft cabin; Mechanical Engineering (0548)